Salivary miRNAs as auxiliary liquid biopsy biomarkers for diagnosis in patients with oropharyngeal squamous cell carcinoma: a systematic review and meta-analysis - Nguyen, Huy; Nonaka, Taichiro (Frontiers in Genetics, 2024)
Objective: The healthcare system needs a novel approach to improve and diagnose early oropharyngeal squamous cell carcinoma against its low survival rate. We conduct a systematic review and a comprehensive meta-analysis for the diagnostic role of blood and salivary microRNAs (miRNAs). Methods: An unbiased and thorough literature search in PubMed yielded appropriate data from qualified articles regarding different miRNA biomarkers, method of extraction, research location, and year of publication. Stata was used to calculate the sensitivity, specificity, diagnostic odds ratio, and summary receiver operating characteristic curve. Results: We included 9 studies with 399 qualified oropharyngeal squamous cell carcinoma patients, which yielded a high diagnostic accuracy of blood miRNAs in combination with salivary miRNAs with a sensitivity of 0.70 (p < 0.001), specificity of 0.75 (p = 0.26), diagnostic odds ratio of 7, and an area under the curve of 0.78. Conclusion: Combined blood- and saliva-derived miRNAs demonstrated a high diagnostic accuracy in detecting oropharyngeal squamous cell carcinoma. Systematic review registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024509424.